A new developed approach for EDL induced from a single concentrated force - Bekiroglu, Serkan; Arslan, Guray; Sevim, Baris (TECHNO-PRESS, 2016)
In this study, it is presented that a new developed approach for equivalent area-distributed loading (EADL) induced from a single concentrated force. For the purpose, a full scale 3D steel formwork system was constructed in laboratory conditions. A developed load transmission platform was put on the formwork system and loaded step by step on the mass center. After each load increment, displacement was measured in several crictical points of the system. The developed platform which was put in to slab of formwork to equivalently distribute the load from a point to the whole slab was constituted using I profiles. A 3D finite element model of the formwork system was analyzed to compare numerical displacement results with experimental ones. In experimental tests, difference among the displacements obtained from reference numerical model (model applied EADL) and main numerical model (model applied single load using a load cell via load transmission platform) is about % 13 in avarage. Difference among the displacements obtained from experimental results and main numerical model under 30 kN single load is about % 11 in avarage. The results revealed that the displacements obtained experimentally and numerically are dramatically closed to each other. It is highlighted from the study that the developed approach is reliable and useful to get EDL.
Keywords: 3D steel formwork system; equivalent area distributed loading; laboratory model; load transmission plafform; FINITE-ELEMENT; RC BEAMS; BEHAVIOR; Construction & Building Technology; Engineering; Materials Science